Enhancing Decision Making through Key Information Value - Ramasamy, Ammuthavali; Ahmad, Mohd Sharifuddin (Journal of Informatics and Mathematical Sciences, 2016)
Organizations have embarked upon various strategies that exploit the use of data and information for competitive advantage. We see numerous strategies proposed for organizations namely in areas of business intelligence applications, such as Data Mining. However, these applications do not inform managers the value of information (VoI) that they generate. Management often does not see the value of such information and how they can relate the information to some measure, such as monetary value or critical business decisions. This produces a gap where managers are unable to identify key information that is important to their business roles with the ability of the technology provided to identify these valuable data. This paper provides an insight to the value of information (VoI) in management and proposes a conceptual model to identify and classify key information value for managers and administrators at all levels of management. The study begins by analyzing revenue-related business processes to identify key information that directly influence the business performance. Qualitative data collection is conducted to solicit information relating to the execution of the business processes to capture other relevant information. A framework is developed to identify and classify the key data and information based on an identified set of criteria for each level of management. This research produces Key Information Value Identification and Classification Framework, which is very useful for companies to enhance their decision-making process at every level or management.